2000
DOI: 10.2135/cropsci2000.402470x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Laboratory Seed Quality Tests and Field Emergence of Common Bean Seed

Abstract: In cool climates, early planting of bean (Phaseolis vulgaris L.) is recommended to assure a longer vegetative growth period. Early planting exposes seed to unfavorable conditions and the commonly used standard germination test cannot predict field emergence. The objective of this work was to examine the relationships between various seed quality tests and field emergence of common bean seeds. Thirty‐nine strains and cultivars of bean were tested in the field and laboratory over 3 yr. Each year seed samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 13 publications
6
25
0
3
Order By: Relevance
“…Field emergence significantly declined in seeds obtained from June (47.6%) and July (46.2%) planted crops. The greater field emergence of seeds from early planted crop could be attributed to availability of longer growing period for dry matter accumulation, seed development, seed filling and proper maturation in comparison to the seeds from late planted crop and thus our findings are in total agreement concerning, Field emergence % age [8].…”
Section: Introductionsupporting
confidence: 76%
“…Field emergence significantly declined in seeds obtained from June (47.6%) and July (46.2%) planted crops. The greater field emergence of seeds from early planted crop could be attributed to availability of longer growing period for dry matter accumulation, seed development, seed filling and proper maturation in comparison to the seeds from late planted crop and thus our findings are in total agreement concerning, Field emergence % age [8].…”
Section: Introductionsupporting
confidence: 76%
“…Seed tolerant of cooler temperature is able to maintain cell membrane integrity. Traits such as the semi-hard seed coat (Taylor and Dickson 1987), reduced rate of water imbibition and electrolyte leakage (Kolasinska et al 2000) have all been used as screening tools. In our study, water imbibition and electrolyte leakage were not considered.…”
Section: Results and Discussion Studymentioning
confidence: 99%
“…Genotypes and seed lots of specific genotypes have been found to differ in their ability to germinate in cold soil (Pollock et al 1969;Jennings 1999;Kolasinska et al 2000). Much research on bean germination under controlled cold temperatures has used constant temperature regimes, but alternating temperatures appear to be a strong signal for inducing germination (e.g., Zaiter et al 1994).…”
mentioning
confidence: 99%
“…It doesn't completely estimate the seedling emergence performance because field conditions are rarely optimum for germination, which adversely affect the emergence and subsequent seedling growth (Hampton and TeKrony, 1995;Kolasinska et al, 2000;Khan et al, 2010). Tekrony and Egli (1977) reported the standard germination exhibited a significant correlation with field emergence of soybean only if favorable field conditions have been available while Makkawi et al (1999) demonstrated the standard germination was the only test to be useful for predicting field emergence of lentil.…”
Section: Introductionmentioning
confidence: 99%